2003
DOI: 10.1002/cbic.200390025
|View full text |Cite
|
Sign up to set email alerts
|

Polyglycine II Nanosheets: Supramolecular Antivirals?

Abstract: Tetraantennary peptides [glycine(n)-NHCH(2)](4)C can form stable noncovalent structures by self-assembly through intermolecular hydrogen bonding. The oligopeptide chains assemble as polyglycine II to yield submicron-sized, flat, one-molecule-thick sheets. Attachment of alpha-N-acetylneuraminic acid (Neu5Acalpha) to the terminal glycine residues gives rise to water-soluble assembled glycopeptides that are able to bind influenza virus multivalently and inhibit adhesion of the virus to cells 10(3)-fold more effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 32 publications
2
49
0
Order By: Relevance
“…We analyzed conceivable ways of [Gly 7 -NHCH 2 ] 4 C packaging in tectomers and choose the model, in which [Gly 7 -NHCH 2 ] 4 C monomers with paired antennae in polyglycine II conformation are situated normally to the tectomer plane. Thickness of this model structure is in the best agreement to thickness of tectomers measured by scanning force microscopy (SFM), 4.5 nm [6]. Later we showed that tectomers can be formed on a surface more readily than in solution volume, particularly on mica due to the opposite charges of terminal NH 2 groups and mica surface [7].…”
Section: Introductionsupporting
confidence: 77%
See 4 more Smart Citations
“…We analyzed conceivable ways of [Gly 7 -NHCH 2 ] 4 C packaging in tectomers and choose the model, in which [Gly 7 -NHCH 2 ] 4 C monomers with paired antennae in polyglycine II conformation are situated normally to the tectomer plane. Thickness of this model structure is in the best agreement to thickness of tectomers measured by scanning force microscopy (SFM), 4.5 nm [6]. Later we showed that tectomers can be formed on a surface more readily than in solution volume, particularly on mica due to the opposite charges of terminal NH 2 groups and mica surface [7].…”
Section: Introductionsupporting
confidence: 77%
“…Analyzing possible ways of the peptides packing into such crystalline layers we have fixed our attention on the variants presented in Scheme 2. Thus, for the tetraantennary peptide, "2+2" packaging, in which two coplanar pairs of peptide antennae are oppositely directed, seems to be favorable as also is for solution-formed tectomer platelets studied earlier [6]. The triantennary molecule are presumably packed in tectomer layer as a trident ("3+0" packaging).…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations